Competition Policy and Price Fixing - LOUIS KAPLOW (Princeton University Press, 2013)
The rule against price fixing is the least controversial prohibition in competition law throughout the world, and the practice is universally subject to the law’s harshest penalties. There is, however, far less consensus than meets the eye on what constitutes price fixing and on how legal regimes should determine its presence. More surprising, prevalent understandings are not grounded in oligopoly theory even though modern competition policy is widely taken to rest on economic substance rather than legal formalism. This book’s central aim is to provide an analytical foundation for designing policy toward coordinated price elevation in oligopolistic industries. In rough terms, the proper methodology is straightforward. First, one articulates the problem and undertakes welfare-based analysis to specify the benefits and costs of attempts to control it. Next, one examines how coordinated price elevation is best detected, attending to the error costs associated with different types of proof. Finally, one sets appropriate sanctions. These elements of a direct approach have received remarkably little attention in the literature. Instead, commentators, government agencies, and courts display some tendency to focus on penalizing certain sorts of interfirm communications that facilitate coordinated oligopoly pricing. Although such punishment has great value for unmasked cartels, systematic comparison with a more direct, functional approach reveals conventional means to be inferior and in important respects counterproductive in cases without smoking-gun evidence. In those settings, a direct approach dominates the conventionally favored communications-based prohibition in that the former targets situations that involve both greater social harm and less risk of chilling desirable behavior than those most likely to generate liability under the latter. The direct approach is also less difficult to administer, contrary to conventional wisdom.